Implementation of Drama Media as an Educational Strategy for Sustainable Waste Management for Early Childhood in Weleri Village - Ilham Dhiya Ul Haq Ramadhan; Rina Ariyani; Asyif Faozi (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The use of drama is needed as a learning medium to increase awareness of waste management in early childhood in Weleri Village. Through observation and interviews, this study found that the waste problem in Weleri Village is quite serious. To overcome this problem, researchers used a drama approach to convey the concept of 5R (refuse, reduce, reuse, repair, recycle) to students of Kanisius Elementary School. The results showed that drama succeeded in attracting students' interest and increasing their understanding of the importance of waste management. Students actively participated and gave positive responses to drama activities. In conclusion, drama can be an effective tool to educate early childhood about waste management and encourage more environmentally friendly behavior.